Barriers and Facilitators to Help-Seeking for Individuals with Posttraumatic Stress Disorder (PTSD): A Systematic Review - Smith, Jennifer R. (Université d'Ottawa / University of Ottawa, 2016)
Background Posttraumatic stress disorder (PTSD) brings with it diagnostic symptoms that can be debilitating and persist for years. Left untreated, PTSD can have far-reaching and damaging consequences – for the individual, families, communities, and society at large. While early detection and intervention is recognized as key to the effective treatment of PTSD, many who suffer from PTSD do not seek essential health services. The aim of this study was to answer the research question: based on existing literature, what are the barriers and facilitators to help-seeking for individuals with PTSD? Methods A systematic review, modeled on the Joanna Briggs Institute (JBI) methodology for systematic reviews, examined studies cited in PsycINFO, Medline, Embase, CINAHL and PILOTS published from January 2000 to November 2015. Eligible studies measured barriers and facilitators to help-seeking for adults with PTSD. Two reviewers independently screened citations and double data extraction was exercised. Results Of 1,759 potentially relevant citations, sixteen studies were included, published between 2003 and 2015 and based in five countries, predominantly within the United States (n=12). Thirteen studies focused on military as a target population. Eight principal barrier themes and seven principal facilitator themes were identified, under which supportive subthemes were categorized. Conclusions In identifying prominent barriers and facilitators to help-seeking for individuals with PTSD, this review highlights opportunities to inform policies and programs that educate and promote PTSD knowledge and recognition, reduce public and personal stigma, improve access and availability of care, and encourage social support for patients and families living with PTSD.
Keywords: Posttraumatic Stress Disorder; PTSD; Help-Seeking; Barriers; Facilitators